Exergy analysis associated with heat transfer during heating of slab products - Akpinar, Ebru (Inderscience Enterprises Ltd, 2010)
This study deals with an exergy analysis associated with the transient heat transfer taking place during heating of slab shaped products. First, the Dincer and Dost's analytical technique is applied to determine the heat transfer coefficient and surface temperatures using the centre temperatures measured during the heating of slab products. Second, an exergy analysis is conducted as associated with the transient heat transfer to study the change of Exergetic Heating Effectiveness (ExHE) and exergy efficiency with temperature, velocity and time.
Keywords: EHE; energetic heating effectiveness; ExHE; exergetic heating effectiveness; exergy efficiency; transient heat transfer; heat transfer coefficient